Efficacy of perioperative cefuroxime as a prophylactic antibiotic in women requiring caesarean section: A systematic review. (November 2019) - Alrammaal, Hanadi H.; Batchelor, Hannah K.; Morris, R. Katie; Chong, Hsu P.
Abstract: Intravenous (IV) Cefuroxime (CFX) is widely used in Caesarean Section (CS) as a prophylactic antibiotic. The objective of this systematic review to compare CFX concentration in maternal blood and adipose tissue with the incidence of surgical site infection (SSI) following IV CFX in non-obese and obese women undergoing CS. A search in Medline, EMBASE, Cochrane, Web of Science, CINHAL Plus, Scopus and Google Scholar was conducted without language or date restrictions. Published articles or abstracts reporting CFX concentration or rates of SSI following CFX IV administration in adult women requiring CS were included. Studies were screened by title and abstract. Quality of studies was assessed via the ClinPK Statement checklist (Pharmacokinetics studies), or Joanna Briggs Institute Critical Appraisal Tools (SSI studies). The Cochrane Effective Practice and Organisation of Care checklist evaluated the risk of bias (SSI studies). There were no studies evaluating CFX concentrations in obese women undergoing CS. For non-obese women, CFX plasma concentrations ranged from 9.85 to 95.25 mg/L within 30–60 min of administration (1500 mg dose; 4 articles, n = 108 women). Plasma CFX concentrations were above the minimum inhibitory concentration (8 mg/L) for up to 3 h post-dose. No studies reported on CFX concentration in adipose tissue. Reported rates of SSI were 4.7% and 6.8% after administration of a single 1500 mg dose of CFX administrated after cord clamping (n = 144 women). There is limited data on pharmacokinetics of CFX for CS. There were no studies that reported CFX concentrations or SSI in obese women.